CURRENT STATUS AND MEASURES FOR MANAGING THE ASSESSMENT OF LEARNING OUTCOMES IN COLLEGES IN NGHE AN PROVINCE - Nguyen Huu Hang; Nguyen Nhu An (Tạp chí Khoa học)
This article analyzes and evaluates the current status of managing the assessment of students' learning outcomes in colleges (within the vocational education sector) in Nghe An province. The survey and analysis are conducted based on the essential functions of management activities: planning, organizing, directing, and evaluating. Additionally, factors affecting the management of the assessment of students' learning outcomes are surveyed according to their levels of impact and influence. The findings on the effectiveness of implementing these management functions reveal the current status of managing the assessment of learning outcomes in colleges in Nghe An province. These findings form the basis for proposing measures to improve the effectiveness of managing learning outcome assessment activities in colleges across the province.